2022
DOI: 10.1177/03331024221079296
|View full text |Cite
|
Sign up to set email alerts
|

Headache characteristics and postoperative course in Chiari I malformation

Abstract: Background Chiari I malformation typically presents with cough headache. However, migraine-like or tension-type-like headaches may also occur. There are limited publications on Chiari I malformation-associated headache semiologies and the effect of foramen magnum decompression on different headache types. Methods A retrospective analysis complemented by structured phone interviews was performed on 65 patients with Chiari I malformation, treated at our hospital between 2010 and 2021. Headache semiology (accordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Milhorat et al, in their study by observing 364 patients, stated that 86% of these patients had headache and most commonly localized pain in the occipital and nuchal region, exacerbated by valsalva-like maneuvers, and in the form of crushing and pressure ( 14 ). Similarly, Thunstedt et al reported that 63% of CM1 patients had headache, and 80% of this headache was localized in the occipital and nuchal regions ( 15 ). In our study, we found that there was a 61% headache and the localization was in a similar region.…”
Section: Discussionmentioning
confidence: 92%
“…Milhorat et al, in their study by observing 364 patients, stated that 86% of these patients had headache and most commonly localized pain in the occipital and nuchal region, exacerbated by valsalva-like maneuvers, and in the form of crushing and pressure ( 14 ). Similarly, Thunstedt et al reported that 63% of CM1 patients had headache, and 80% of this headache was localized in the occipital and nuchal regions ( 15 ). In our study, we found that there was a 61% headache and the localization was in a similar region.…”
Section: Discussionmentioning
confidence: 92%
“…We found that approximately 8% of pediatric/adolescent (47) and 14.2% of adult (48) cases reported migraines, suggesting that the risk in CIM patients and patients with primary headache is comparable and atypical headache is often an incidental finding. Therefore, some scholars conclude that the presence of atypical headaches may be coincidental and mechanistically distinct from the specific symptoms of CIM (15,16). Consequently, conservative treatment is recommended (2,6,37).…”
Section: Surgery For Typical Headachementioning
confidence: 99%
“…Although relief of atypical headaches is achieved in many cases of CIMs after PFD, Thunstedt et al. (15) noted the effect was smaller than a typical headache, which cannot be ruled out as a result of the natural course of primary headache as well as the placebo effect of surgery. Notably, Thunstedt pointed out that the relationship between atypical headache and CIM remains unclear and requires further study.…”
Section: Surgery For Typical Headachementioning
confidence: 99%
See 1 more Smart Citation
“…CM-I are primary signs of compression caused by herniated cerebellar tonsils or SM. 4 Congenital CM-I is usually treated surgically, although acquired CM-I can be treated etiologically. Surgical options for the treatment of CM-I include posterior fossa decompression (PFD), posterior fossa decompression with duraplasty (PFDD), and posterior fossa decompression with resection of tonsils (PFDRT).…”
mentioning
confidence: 99%